Using Concept Maps and Fuzzy Set Information Retrieval Model to Dynamically Personalize RSS Feeds - Ismail, Heba Mahmoud (2011)
A Master of Science Thesis in Engineering Systems Management submitted by Heba Mahmoud Ismail entitled, "Using Concept Maps and Fuzzy Set Information Retrieval Model to Dynamically Personalize RSS Feeds," January 2011. Available are both soft and hard copies of the thesis.